Blank canvas : my so-called artist's journey. Volume 2 - Higashimura, Akiko (Seven Seas Entertainment, 2019)
"A RUDE AWAKENING. Thanks to Hidaka-sensei's intensive training, Akiko manages to get through her art school exams. She's one step closer to seeing her dreams come true...or so she thinks!"--Page [4] of cover.